Effect of vector-expressed shRNAs on hTERT expression - Guo, Ying (World J Gastroenterol, 2005)
AIM: To study the effect of short hairpin RNAs (shRNAs) expressed from DNA vector on hTERT expression. METHODS: Oligonucleotides coding for four shRNAs against hTERT were cloned into a mammalian shRNA expression vector pUC18U6 to form pUC18U6ht1-4, which were then introduced into HepG2 cells by using liposome-mediated transfection. HepG2 cells transfected by pUC18U6 and pUC18U6GFPsir, which expressed shRNA against green fluorescent protein (GFP), were used as controls. hTERT mRNA in the transfected cells were quantified by using real-time fluorescent RT-PCR. RESULTS: Among the four shRNAs against hTERT, two decreased the hTERT mRNA level. Compared with the controls, pUC18U6ht which expressed the two shRNAs reduced hTERT mRNA by 39% and 49% (P<0.05). CONCLUSION: hTERT expression is inhibited by the shRNAs expressed from the DNA vector.